2017
DOI: 10.1159/000481852
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>APOE</i></b> ε4 Genotype and Cognitive Reserve Effects on the Cognitive Functioning of Healthy Elders

Abstract: Aim: To test the association between cognitive performance and APOE genotype, and to assess potential modifications of this association by sociodemographic and neuroanatomical factors in a sample of 74 healthy elders. Methods: Firstly, we explored the isolated role of the APOE ɛ4 genotype (i.e., APOE4) in different neuropsychological tests, and then the effects of its interaction with sociodemographic (i.e., age, gender, and educational level) and neuroanatomical (i.e., hippocampal volumes) variables. Subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 69 publications
(79 reference statements)
1
11
1
Order By: Relevance
“…More recently, Foster and coworkers [11] reported that, when the statistical methods removed the effects due to the inclusion of MCIs (considering them as prodromal AD cases), the significant influence of APOE4 vanished. A recent investigation by our group also reinforced the preclinical/prodromal assumption [12]. Inspired by Foster et al's study [11], we evaluated APOE4's effects on cognitive performance in a sample of healthy aged controls and observed that APOE4 carriers exhibited a significantly poorer performance on several cognitive domains, but such effect was explained by the group with a higher risk of presenting cognitive deterioration.…”
Section: Introductionmentioning
confidence: 78%
“…More recently, Foster and coworkers [11] reported that, when the statistical methods removed the effects due to the inclusion of MCIs (considering them as prodromal AD cases), the significant influence of APOE4 vanished. A recent investigation by our group also reinforced the preclinical/prodromal assumption [12]. Inspired by Foster et al's study [11], we evaluated APOE4's effects on cognitive performance in a sample of healthy aged controls and observed that APOE4 carriers exhibited a significantly poorer performance on several cognitive domains, but such effect was explained by the group with a higher risk of presenting cognitive deterioration.…”
Section: Introductionmentioning
confidence: 78%
“…Cognitive variations in healthy elders within the normal range may be determined by demographic factors, basal cognition, and APOE genotyping that were not systematically taken into account in multivariate models. In fact, male gender, low level of education, and mainly the presence of APOE4 allele have been associated with worst cognitive trajectories in non-demented elders (Bretsky et al, 2003; Honea R. et al, 2009; Honea R. A. et al, 2009; Zehnder et al, 2009; Haller et al, 2017; Li et al, 2017; Lin et al, 2017) but negative or ambiguous data have also been reported (Van Gerven et al, 2012; López et al, 2017; Min, 2018). In the present study, higher MMSE scores are associated with higher risk of cognitive decline in this series.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study need to be interpreted in the light of several limitations. The results of several investigations into the genetic contributions to HAND suggest that the harmful effects of ApoE ε4 on cognitive function may be likely to be expressed at a later age (Valcour et al 2004;Pomara et al 2008;Panos et al 2013;Mukerji et al 2016;López et al 2017). Such a temporally mediated effect could explain some of the divergent literature findings regarding the role of ApoE in HAND.…”
Section: Discussionmentioning
confidence: 99%